Socioeconomic inequalities in suicide mortality before and after the economic recession in Spain - Carme Borrell; Marc Marí-Dell'Olmo; Mercè Gotsens; Montse Calvo; Maica Rodríguez-Sanz; Xavier Bartoll; Santiago Esnaola (BMC, 2017)
Abstract Background An increase in suicide mortality is often observed in economic recessions. The objective of this study was to analyse trends in socioeconomic inequalities in suicide mortality before and during the economic recession in two geographical settings in Spain. Methods This study analyses inequalities in mortality according to educational level during 3 different time periods based on individual data from the Basque Country and Barcelona city. We analysed suicide mortality data for all residents over 25 years of age from 2001 to 2012. Two periods before the crisis (2001-2004 and 2005-2008) and another during the crisis (2009-2012) were studied. We performed independent analyses for sex, age group, and for the two geographical settings. We fit Poisson regression models to study the relationship between educational level and mortality, and calculated the relative index of inequality (RII) and the slope index of inequality (SII) as comparative measures. Results For men in the Basque Country, all RII values for the three time periods were similar and almost all were greater than 2; in Barcelona the RII values were generally lower. The SII values for Barcelona tended to decrease over time, whereas in the Basque Country they showed a U-shaped pattern. Among women aged 25-44 years we found an association between educational level and suicide mortality during the first time period; however, we found no clear association for other age groups or time periods. Conclusion This study within two geographical settings in Spain shows that trends in inequalities in suicide mortality according to educational level remained stable among men before and during the economic recession.